Implementación de la alternativa de mejora en el proceso de producción de la cerveza artesanal tipo ale en la empresa Green Hops (2017)
Green Hops, located in the Municipality of Chia-Cundinamarca is a company dedicated to the manufacture of artisan beer, one of the industries that at national level is having an accelerated growth and a market that is generating different opportunities for the investors. Despite this, the company Green Hops in its manufacturing process has had drawbacks due to lack of precision in determining stages during the process, such as maceration, grinding, filtration and fermentation, which in turn generates an increase in Production times, decreases in the quality of the final product (eg turbidity, alcohol levels, suspended solids, among others), and even loss of production lots. In the case of Green Hops, it has been identified that the work of the operator and the conditions implemented in the process are the main cause that the results of the manufacture of the beer are not as expected, causing losses of raw material, inputs, payment Overtime to operators, delays in time, batch losses and a low quality of the final product. For this reason, the analysis and improvement of the determinant stages of the process is a fundamental point to make an efficient and profitable process.